Beta-Amino Carboxylate (BAC) non-aqueous physical solvents for enhanced CO2 separations in pre-combustion carbon capture, industrial CO2 capture, and biogas upgrading processes - Jeffrey T. Culp; Robert L. Thompson; Kathryn H. Smith; David Hopkinson; Nicholas Siefert (International Journal of Greenhouse Gas Control, 2025)

The impact of leaf-wood separation algorithms on aboveground biomass estimation from terrestrial laser scanning - Shilin Chen; Hans Verbeeck; Louise Terryn; Wouter A.J. Van den Broeck; Matheus Boni Vicari; Mathias Disney; Niall Origo; Di Wang; Zhouxin Xi; Chris Hopkinson; Wenxia Dai; Meilian Wang; et al. (Remote Sensing of Environment, 2025)

TEA of the CO2 capture process in pre-combustion applications using thirty-five physical solvents: Predictions with ANN - Husain E. Ashkanani; Rui Wang; Wei Shi; Nicholas S. Siefert; Robert L. Thompson; Kathryn H. Smith; Janice A. Steckel; Isaac K. Gamwo; David Hopkinson; Kevin Resnik; Badie I. Morsi (International Journal of Greenhouse Gas Control, 2023)

Performance of hydrophobic physical solvents for pre-combustion CO2 capture at a pilot scale coal gasification facility - Kathryn H. Smith; Husain E. Ashkanani; Robert L. Thompson; Jeffrey T. Culp; Lei Hong; Mike Swanson; Joshua Stanislowski; Wei Shi; Badie I. Morsi; Kevin Resnik; David P. Hopkinson; Nicholas S. Siefert (International Journal of Greenhouse Gas Control, 2023)

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Climate research priorities for policy-makers, practitioners, and scientists in Georgia, USA - Murray A. Rudd; Althea F. P. Moore; Daniel Rochberg; Lisa Bianchi-Fossati; Marilyn A. Brown; David D’Onofrio; Carrie A. Furman; Jairo Garcia; Ben Jordan; Jennifer Kline; L. Mark Risse; Patricia L. Yager; et al. (Environmental Management, 2018)

Growth of riparian cottonwoods: heterosis in some intersectional Populus hybrids and clonal expansion of females - Stewart B. Rood; Lori A. Goater; David McCaffrey; Joshua S. Montgomery; Chris Hopkinson; David W. Pearce (Trees, 2017)

A Word to the Wise: Advice for Scientists Engaged in Collaborative Adaptive Management - Peter Hopkinson; Ann Huber; David S. Saah; John J. Battles (Environmental Management, 2017)

Canine TCOF1; cloning, chromosome assignment and genetic analysis in dogs with different head types - Kim E. Haworth; Ira Islam; Matthew Breen; Wendy Putt; Eleni Makrinou; Matthew Binns; David Hopkinson; Yvonne Edwards (Mammalian Genome, 2001)

Human succinate dehydrogenase: Biochemical and genetic characterization - Marie-Anne Shaw; Yvonne Edwards; David A. Hopkinson (Biochemical Genetics, 1981)

Characterization of human carbonic anhydrase III from skeletal muscle - Nicholas Carter; Stephen Jeffery; Alan Shiels; Yvonne Edwards; Terry Tipler; David A. Hopkinson (Biochemical Genetics, 1979)